2018
DOI: 10.1016/j.neuron.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Biogenesis Requires Axonal Transport of Lysosome-Related Vesicles

Abstract: Nervous system function relies on the polarized architecture of neurons, established by directional transport of pre- and postsynaptic cargoes. While delivery of postsynaptic components depends on the secretory pathway, the identity of the membrane compartment(s) supplying presynaptic active zone (AZ) and synaptic vesicle (SV) proteins is unclear. Live imaging in Drosophila larvae and mouse hippocampal neurons provides evidence that presynaptic biogenesis depends on axonal co-transport of SV and AZ proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
156
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(177 citation statements)
references
References 74 publications
(128 reference statements)
19
156
1
1
Order By: Relevance
“…Also, transcripts coding for membrane proteins including endoplasmic reticulum proteins, such as Ergic1, Calr or Sec62, were diminished in the vGLUT1 + sorted synaptosomes. There was also a clear depletion of transcripts coding for integral synaptic vesicle proteins ( Fig 4D,F), consistent with a recent report of somatic vesicle biogenesis and transport (31). Of note, among the 468 transcripts enriched in vGLUT1 + terminals, 62 were known targets of the RNA-binding Fragile X Mental Retardation Protein (FMRP), the loss of which causes fragile X syndrome ( Fig.…”
Section: The Presynaptic Transcriptome Of Vglut1+ Terminalssupporting
confidence: 90%
“…Also, transcripts coding for membrane proteins including endoplasmic reticulum proteins, such as Ergic1, Calr or Sec62, were diminished in the vGLUT1 + sorted synaptosomes. There was also a clear depletion of transcripts coding for integral synaptic vesicle proteins ( Fig 4D,F), consistent with a recent report of somatic vesicle biogenesis and transport (31). Of note, among the 468 transcripts enriched in vGLUT1 + terminals, 62 were known targets of the RNA-binding Fragile X Mental Retardation Protein (FMRP), the loss of which causes fragile X syndrome ( Fig.…”
Section: The Presynaptic Transcriptome Of Vglut1+ Terminalssupporting
confidence: 90%
“…We found that activity-dependent MT nucleation at boutons is required for interbouton SV motility, and to allow neurotransmitter release (Figures 3 and 4). Arl8b facilitates the Kif1A mediated motility of both SVs and PLVs, which coordinate the anterograde transport of packets of AZ and SV proteins in developing neurons during presynaptic biogenesis (30,31,35). In addition, Kif1A was recently implicated in synaptic cargo anterograde delivery to en passant boutons using dynamic MTs as tracks (23).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, all three mRNAs are high confidence targets of FMRP in granule neurons ( Table 2). It is thought that the coordinated delivery of these active zone components to presynaptic domains by anterograde transport along microtubules using kinesin motors (including Kif1a) allows for their growth [169][170][171][172] . Notably, the top ranked mRNA target of FMRP in granule cells is Rapgef4 which encodes Epac2/RapgefII, a guanine nucleotide exchange factor for Rap1 and a sensor of cAMP levels, which are altered in both the mouse model and human patient cells [173][174][175][176] [190][191][192][193] and Emily Osterweil and colleagues have identified lovastatin as an ERK inhibitor which has shown efficacy in mouse 130 and rat 132 FXS models.…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%